2019
DOI: 10.1248/bpb.b18-00820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adverse Reactions Caused by Potentially Inappropriate Prescriptions and Related Medical Costs That Are Avoidable Using the Beers Criteria: The Japanese Version and Guidelines for Medical Treatment and Its Safety in the Elderly 2015

Abstract: We conducted a retrospective study to investigate adverse drug reactions and associated medical costs among elderly individuals that could be avoided if pharmacotherapy was performed in accordance with the Beers Criteria: the Japanese Version (BCJV) and Guidelines for Medical Treatment and Its Safety in the Elderly 2015 (GL2015). Patients aged at least 65 years who were either hospitalized at Gifu Municipal Hospital between October 1 and November 30, 2014 (n 1236) or had outpatient examinations at Gifu Municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…Of these, 103 articles were excluded, mainly because studies reported a different outcome of interest ( n = 58). The final screening identified 63 studies 33–95 suitable for inclusion in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 103 articles were excluded, mainly because studies reported a different outcome of interest ( n = 58). The final screening identified 63 studies 33–95 suitable for inclusion in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…evaluated the mean cost of PIMs using STOPP v2 and determined that the cost associated with PIM use was €18.75 ± 4.24 per patient per month (€225.14 ± 50.91 per patient per year), with opioids accounting for the highest percentage of the expenditure. Similarly, Tachi et al 88 . calculated the extra cost for treatment of adverse reactions per inpatient who was prescribed drugs listed in the Beers Criteria–Japanese Version and Guidelines for Medical Treatment and its Safety in the Elderly 2015 and was estimated to range from 497 to 13 371 yen per patient (≈7–180 AUD), which corresponds to a national cost of 2.18–381.42 (≈0.03–5 AUD) billion yen per year.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations